Meta-Analysis of Breastfeeding’s Impact on Pediatric Immune Modulation and Risk Reduction of Childhood Lymphomas - Mahmood, Talat; Atta Ullah; Raza, Wasiq; Muhammad, Saqib; Nabuwat Khaksar; Ansari, Adila Islam; Maliha Rohi; Khan, Kainat; Atiq Ur Rehman; Altaf, Jalwa (Indus Journal of Bioscience Research, 2024)
Background: Breastfeeding offers nutritional and immunological benefits, enhancing immune system development in newborns. It has gained research interest for its potential to reduce childhood cancer risk, particularly lymphomas, though evidence remains limited. This meta-analysis evaluates breastfeeding’s protective role against childhood lymphomas. Objective: To assess the impact of breastfeeding duration, exclusivity, and geographical variability on childhood lymphoma risk. Methods: A systematic review and meta-analysis was conducted per PRISMA guidelines. Relevant studies were retrieved from PubMed, Scopus, and Cochrane Library. Inclusion criteria included breastfeeding exposure, lymphoma outcomes, and effect measures (ORs). Quality assessment and data extraction were performed using a standardized checklist. Meta-analysis employed a random-effects model. Results: The analysis included 24 studies comprising over 150,000 children. Breastfed children showed a 22% lower risk of childhood lymphomas (OR: 0.78; 95% CI: 0.72–0.85; p < 0.001). Longer breastfeeding (>6 months) and exclusivity provided stronger protection. Subgroup analysis indicated a more significant effect for non-Hodgkin’s lymphoma (OR: 0.74) than Hodgkin’s lymphoma (OR: 0.83). Geographic variability was observed, with Asia showing the strongest protective effects. Conclusion: Exclusive breastfeeding and prolonged breastfeeding substantially reduce childhood lymphoma risk, highlighting breastfeeding as a cost-effective public health strategy for cancer prevention. Further research is needed to explore underlying biological and psychological mechanisms and regional differences. Breastfeeding promotion should remain a global priority to improve pediatric health and reduce childhood cancer burden.